Investigation on the Hydrodynamic Performance of An Ultra Deep Turret-Moored FLNG System - 赵文华 杨建民 胡志强 肖龙飞 彭涛 (China ocean engineering, 2012)
Hydrodynamic performance of an ultra deep turret-moored Floating Liquefied Natural Gas （FLNG） system is investigated. Hydrodynamic modeling of a turret-moored FLNG system, in consideration of the coupling effects of the vessel and its mooring lines, has been addressed in details. Based on the boundary element method, a 3-D panel model of the FLNG vessel and the related free water surface model are established, and the first-order and second-order mean-drift wave loads and other hydrodynamic coefficients are calculated. A systematic model test program consisting of the white noise wave test, offset test and irregular wave test combined with current and wind, etc. is performed to verify the numerical model. Owing to the depth limit of the water basin, the model test is carried out for the hydrodynamics of the FLNG coupled with only the truncated mooring system. The numerical simulation model features well the hydrodynamic performance of the FLNG system obtained from the model tests. The hydrodynamic characteristics presented in both the numerical simulations and the physical model tests would serve as the guidance for the ongoing project of FLNG system.